Proses Transesterifikasi Biodiesel Menggunakan Katalis Sodium Methoxide Dan Katalis Berbasis Karbon Aktif Dari Tempurung Kelapa Yang Diimpregnasi NaOH - Meygi Rezablina; Mustain Zamhari; Ahmad Zikri (Jurnal Serambi Engineering, 2023)
Biodiesel is one of the renewable energies that can be obtained by converting triglycerides into methyl esters by transesterification process. Used cooking oil is heated with anhydrous methanol which is added with an acid catalyst or base catalyst. The catalyst has a role as a substance to reduce the activation energy of fatty acids in used cooking oil to increase the reaction rate. In this study, Sodium methoxidealkaline catalyst and NaOH-impregnated activated carbon base catalyst were used. Activated carbon catalyst using variation of concentration of activated carbon 1N, 2N, 3N, 4N, and 5N for 18 hours, 21 hours, and 24 hours and the use of sodium methoxidecatalyst with variation of oil: methanol ratio 1:3, 1:6, 1:9, 1:12, 1:15. The results showed that the biodiesel yield using carbon catalyst was 98.2%, 2% w/w catalyst with oil: methanol ratio 1:12 at 60℃ for 120 minutes. The best result of biodiesel using sodium methoxidecatalyst is 87.65%, catalyst 1.25% w/w with ratio 1:12, temperature 60℃ for 120 minutes. Keyword :  Active Carbon, Biodiesel, Catalyst, Sodium Methoxide, Transesterification